Lipidated proteins: Spotlight on protein-membrane binding interfaces. (September 2017) - Ray, Arjun; Jatana, Nidhi; Thukral, Lipi
Abstract: The covalent attachment of lipids to proteins is a fundamental property of all living cells. These lipidated or lipid-modified proteins are directly targeted to the membranes and display diverse functional roles that are critical to cell function such as membrane signaling and trafficking. All lipidated proteins have been classified by the type of chemical moieties that are attached to them mainly palmitoylation, myristoylation, prenylation, cholesterylation, and addition of the Glycosylphosphatidyl inositol (GPI) anchor. Although the distinct hydrophobic lipid moiety largely dictates the functional compartmentalization, it also facilitates membrane trafficking and triggers a wide range of signaling pathways in cellular growth. In this review, we will focus on mechanistic insights underlying their membrane attachment, with a view to understand the regions that contribute to protein-membrane interface specificity. We also present a computational case study to report how different membrane lipids modulate insertion of the lipidated LC3 protein. Finally, in this review, we demonstrate the potential of regulating lipid modifications that are essential for cell survival and we discuss the concepts regarding their role in disease and therapeutics.